2001
DOI: 10.1536/jhj.42.255
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Syncope Induced by a Combination of Cibenzoline and Angiotensin Converting Enzyme Inhibitor.

Abstract: SUMMARYA 65-year-old Japanese woman with dilated cardiomyopathy, hypothyroidism and refractory sustained ventricular tachycardia experienced a near-death hypoglycemic syncope. The attack seemed to be induced by a high level of serum insulin, probably due to cibenzoline and by concomitant use of an angiotensin converting enzyme inhibitor (ACEI). Additionally, decreased food intake because of a severe toothache may have contributed to the deterioration of her condition. This case warns cardiologists that a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, we have reported that the class Ia antiarrhythmic drug, cibenzoline, can directly improve the left ventricular pressure gradient and diastolic function in patients with HCM. 15 However, cibenzoline, which is reported to cause hypoglycemia via insulin oversecretion, 16 may be contraindicated in patients with GSD-IIIa. Treadmill exercise testing and measurements of maximal oxygen consumption have proved helpful in determining which patients may benefit from pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have reported that the class Ia antiarrhythmic drug, cibenzoline, can directly improve the left ventricular pressure gradient and diastolic function in patients with HCM. 15 However, cibenzoline, which is reported to cause hypoglycemia via insulin oversecretion, 16 may be contraindicated in patients with GSD-IIIa. Treadmill exercise testing and measurements of maximal oxygen consumption have proved helpful in determining which patients may benefit from pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%